El bono de desarrollo humano y su incidencia en la reducción de la pobreza a de los beneficiarios del cantón Guano, provincia de Chimborazo, período 2015-2016 - Zuñiga Mosquera, Andrea Lisbeth (2017)
This research project focuses on the impact of the human development bonus on the poverty reduction of the beneficiaries of the canton of Guano, province of Chimborazo, during the period 2015-2016, developing it quantitatively, qualitatively and bibliographically, considering the policies, goals, objectives and methods of measurement intended for the correct execution of this program, in improving the quality of life of the study population. On the other hand the information of each beneficiary is given through tables, graphs, analysis and discussion of results. Thus the content of this research is composed of four chapters detailed below: Chapter I: Reference Framework consists of the problem statement, the general and specific objectives and the justification for the research. In this chapter we can highlight the problem by which the research was developed and the objectives to be fulfilled. Chapter II: Theoretical Framework, is divided into three units, the first consists of the background, definitions, characteristics, components and types of bonds focusing on social aid. The second unit covers the definition, characteristics and types of poverty with their respective forms of measurement. Finally, it is about the evolution of the human development bonus in Ecuador, the legal basis, parameters and guidelines for the selection of beneficiaries, coverage and payment. Chapter III: Methodological Framework is composed of the method, type and design of the research, the number of beneficiaries from a macro and micro population that is as a population and sample to be surveyed to collect the data and process the information of the variables. Chapter IV: Conclusions are drawn up once the research and recommendations have been completed.